N-heterocyclic carbene-catalyzed hydroacylation of unactivated double bonds - Hirano, Keiichi; Biju, Akkattu T.; Piel, Isabel; Glorius, Frank (Journal of the American Chemical Society, 2009)
An intramolecular N-heterocyclic carbene (NHC)-catalyzed hydroacylation of unactivated double bonds is reported. Systematic variation of the catalyst structure revealed an N-mesitylthiazolylidene annulated with a seven-membered ring to be especially reactive. This NHC enables a unique C−C bond-forming reaction to afford substituted chroman-4-ones in moderate to excellent yields, even ones containing all-carbon quaternary centers.